Cities under COVID-19 a systems perspective - Howden-Chapman, Philippa; Gatzweiler, Franz W. Ingenieur-Agronom; Cooper, Rachel 1953-; Luginaah, Isaac (Urban health and wellbeing, 2023)
The 15 international authors of this book live in Brazil, Canada, Cameroon, China, Cuba, European Union, Finland, Gaza Strip, India, Nepal, New Zealand, Nigeria, Sri Lanka, United Kingdom and the United States of America. The authors are linked to the International Science Council’s Urban Health and Wellbeing Programme. In this book the authors analyse the management of COVID-19, which started in late 2019, in their cities. They explain their city’s political, social and economic context, the dynamics of how the pandemic unfolded, drawing on quantitative and visual data, and their reflections on how it was managed. The book concludes with an analysis of the similarities and differences among COVID-19 outcomes in these cities. Using a systems perspective to learn from these experiences can help all cities to improve the governance of pandemics and be better prepared for likely future ones